2016
DOI: 10.24925/turjaf.v4i1.31-35.509
|View full text |Cite
|
Sign up to set email alerts
|

Study on Prevalence of Mycoflora in Wheat Seeds

Abstract: Forty seed sample of wheat (Triticum aestivum) were collected from four locations viz. Chitwan, Kaski, Banke and Lalitpur and tested by blotter method at laboratory during 2013 for determining fungal pathogens associated with wheat seeds in Nepal. Eighteen species representing thirteen genera of fungi were recovered from the seed. Alternaria alternata and Bipolaris sorokiniana were predominant in all the varieties/genotypes from all the locations, where B. sorokiniana was strongly pathogenic in wheat crop. Per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
2
3
0
2
Order By: Relevance
“…The occurrence of Alternaria spp. reached 78%, which is similar to the results reported in different regions by many researchers [2,[11][12][13][14]. The fungi from the genus Alternaria are common members of the mycobiota of wheat grain, but the importance of this fungal group depends on various conditions and the species of pathogens.…”
Section: Discussionsupporting
confidence: 80%
“…The occurrence of Alternaria spp. reached 78%, which is similar to the results reported in different regions by many researchers [2,[11][12][13][14]. The fungi from the genus Alternaria are common members of the mycobiota of wheat grain, but the importance of this fungal group depends on various conditions and the species of pathogens.…”
Section: Discussionsupporting
confidence: 80%
“…Likewise, Hashem (1990) reported the presence of A. niger, A. flavus and B. australiensis on barley seeds in Saudi Arabia. Likewise the fungal species isolated in this study, A. niger, A. flavus, Bipolaris and Rhizopus stolonifera have been recovered from Triticum aestivum seeds (wheat) (Adhikari et al, 2016). Moreover, all isolated fungal species, except B. australiensis, reported in this study were also found on barley grains in Pakistan (Fakhrunnisa, and Ghaffar, 2006).…”
Section: Discussionsupporting
confidence: 68%
“…The representativeness of fungus species was determined by the variety and the location of its cultivation. Alternaria alternata and Bipolaris sorokiniana dominated in all research variants (Adhikari et al, 2016;Adhikari et al, 2018). Twenty-one genera/species were found in Latvia during the period 56 Ukrainian Journal of Ecology, 11(1), 2021 of investigation 2012-2016.…”
Section: Introductionmentioning
confidence: 97%